Konstruksi perempuan dan gender dalam gerakan Tarbiyah di kampus-kampus universitas negeri di Surabaya: sebuah modalitas pembangunan karakter bangsa - Diah Ariani Arimbi (Masyarakat, Kebudayaan dan Politik, 2016)
The Tarbiyah (education) movement in Indonesia today is the best known and has the largest number of members amongst groups in the Dakwah (proselytising) movement that mostly work in Indonesian campuses. However, in contrast to other Islamic revivalist organizations, the Tarbiyah movement, is reformist, and relies heavily on modern interpretations of Islam concerned with democracy, civil society, human rights and equality of women, although these values are understood differently from common Western notions. The group has many female activists but unfortunately until today there has never been any study looking at the ways women has involved in this Tarbiyah movement. This paper aims to explore the numerous and varieties of women‟s activities in this movement, especially in relation the ways women see their rights, roles and sexual identities within their notion of piety. Female and male activists of Tarbiyah movement in Airlangga University (UNAIR), Surabaya State University (UNESA) and Institute of Technology Surabaya (ITS) are respondents in this research. Participation observation and in-depth interviews will used as techniques of data collection. Some finding shows that the Tarbiyah movement‟s espousal of women‟s and gender issues in an Islamic setting complicates even more the dissemination of such issues to the Indonesian public. One important finding indicates that the Tarbiyah conceives that male and female are segregated in nature (biological construction) yet in that segregation lies irreplaceable equality in any sphere and any value. Although many female members of the Tarbiyah movement claim to reject feminism, in particular they reject liberation of women‟s (and men‟s) sexuality, as it is believed to be of Western origin, in fact they subscribe to concepts of sexual equality while maintaining sexual segregation. The rise of the Dakwah movement and its various groups has raised concern in Indonesian society that such groups may pose a threat to civil Islam. However, to see all groups in the Dakwah movement as militant, radical or even fundamentalist is wrong, the complexity of Islamic movements requires careful examination as within these movements groups are fragmented in terms of their interpretations of Islam and its application. Teaching of this Dakwah movement can also be an alternative to national character building as its teachings and morale are in accordance to the values of Indonesian national characters such as honesty, religiousness and others.